Loans on Securities, 1921-32 - Livermore, Shaw (The Review of Economics and Statistics, 1932)
THE widespread interest and concern over the mounting volume of credit based on security collateral in the years I927-30 resulted in a notable improvement in both the quantity and the quality of banking figures relating to such credit, and in the future there will be presumably no such lack of adequate data as hampered analysis in those critical years. In previous years loans on securities had seldom been separated from other loans in banking statistics. At present, however, by the use of the abundant source figures that are at hand, it is possible to construct an estimate of the total volume of security loans, from non-banking as well as banking sources, and to extend this estimate back for a decade. By this means a broad base can be supplied for comparisons and conclusions. Such inclusive estimates have been made for a few recent years.1 There are two series of first importance in making estimates of total collateral loans for the recent period beginning in 1928. The first is the quarterly figure of the Federal Reserve Board showing the total loans on securities for all member banks. On the present quarterly basis this series extends back only to October I928, but it was presented annually as of June 30 for the years beginning with I925. A second figure of basic importance is the annual total of the Comptroller of the Currency for all banking institutions in the country. Since 1929 the classification used by the Comptroller in securing data from the various state banking officials is the same as that used by the Reserve Board in making up the quarterly figure just referred to. Thus the composite figure of the Comptroller, which in past years had not been comparable with other series, will be so in the future, and hence of far greater value. Since under any conditions the figure is dependent upon the cooperation of many state authorities, it is dangerous to place complete reliance upon it; a margin of error always exists in a figure built up from many sources. But a major portion of the total is, of course, furnished by national banks, for which uniformity and homogeneity are possible. Thiis yearly total, with adjustment for loans to banks, is entered on the accompanying table (p. I93) as the suggested banking total for I929, I930, and I93I.2 The less inclusive figures relating to loans on securities became well known during the boom years. The weekly total compiled by a group of member banks in New York City is generally used as an up-to-date weekly barometer of loan conditions. Another figure of special value is the monthly total of borrowings by all members of the New York Stock Exchange. It includes borrowings from non-banking sources that would not otherwise be known. The weekly figure for reporting member banks scattered throughout the country reflects loans made direct to other customers as well as to brokers.